Resuelve las siguientes ecuaciones lineales :
A. x-3/2 + 7 = x - 5 - x/4
B. -3(5-x) /10 -3x/2=7 - 5x/3
C. 3(x+1) /2 - x = x-4/3
D. x+2/2 -3 (x+1) = -5x/2 -2
Respuestas
Respuesta dada por:
39
Resuelve las siguientes ecuaciones lineales :
A. x-3/2 + 7 = x - 5 - x/4
![x-\frac{3}{2}+7=x-5-\frac{x}{4} x-\frac{3}{2}+7=x-5-\frac{x}{4}](https://tex.z-dn.net/?f=x-%5Cfrac%7B3%7D%7B2%7D%2B7%3Dx-5-%5Cfrac%7Bx%7D%7B4%7D)
![x-\frac{3}{2}+7-x=x-5-\frac{x}{4}-x x-\frac{3}{2}+7-x=x-5-\frac{x}{4}-x](https://tex.z-dn.net/?f=x-%5Cfrac%7B3%7D%7B2%7D%2B7-x%3Dx-5-%5Cfrac%7Bx%7D%7B4%7D-x)
![-\frac{3}{2}+7=-5-\frac{x}{4} -\frac{3}{2}+7=-5-\frac{x}{4}](https://tex.z-dn.net/?f=-%5Cfrac%7B3%7D%7B2%7D%2B7%3D-5-%5Cfrac%7Bx%7D%7B4%7D)
![-5-\frac{x}{4}=-\frac{3}{2}+7 -5-\frac{x}{4}=-\frac{3}{2}+7](https://tex.z-dn.net/?f=-5-%5Cfrac%7Bx%7D%7B4%7D%3D-%5Cfrac%7B3%7D%7B2%7D%2B7)
![-5-\frac{x}{4}=\frac{7}{1}-\frac{3}{2} -5-\frac{x}{4}=\frac{7}{1}-\frac{3}{2}](https://tex.z-dn.net/?f=-5-%5Cfrac%7Bx%7D%7B4%7D%3D%5Cfrac%7B7%7D%7B1%7D-%5Cfrac%7B3%7D%7B2%7D)
![-\frac{x}{4}=\frac{21}{2} -\frac{x}{4}=\frac{21}{2}](https://tex.z-dn.net/?f=-%5Cfrac%7Bx%7D%7B4%7D%3D%5Cfrac%7B21%7D%7B2%7D)
![-x=42
x=-42 -x=42
x=-42](https://tex.z-dn.net/?f=-x%3D42%0A%0Ax%3D-42)
B. -3(5-x) /10 -3x/2=7 - 5x/3
![\frac{-3\cdot \left(5-x\right)}{10}-\frac{3x}{2}=7-\frac{5x}{3} \frac{-3\cdot \left(5-x\right)}{10}-\frac{3x}{2}=7-\frac{5x}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-3%5Ccdot+%5Cleft%285-x%5Cright%29%7D%7B10%7D-%5Cfrac%7B3x%7D%7B2%7D%3D7-%5Cfrac%7B5x%7D%7B3%7D)
![\frac{-3\left(5-x\right)}{10}-\frac{3x}{2}+\frac{5x}{3}=7-\frac{5x}{3}+\frac{5x}{3} \frac{-3\left(5-x\right)}{10}-\frac{3x}{2}+\frac{5x}{3}=7-\frac{5x}{3}+\frac{5x}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-3%5Cleft%285-x%5Cright%29%7D%7B10%7D-%5Cfrac%7B3x%7D%7B2%7D%2B%5Cfrac%7B5x%7D%7B3%7D%3D7-%5Cfrac%7B5x%7D%7B3%7D%2B%5Cfrac%7B5x%7D%7B3%7D)
![\frac{14x-45}{30}=7 \frac{14x-45}{30}=7](https://tex.z-dn.net/?f=%5Cfrac%7B14x-45%7D%7B30%7D%3D7)
![\frac{30\left(14x-45\right)}{30}=7\cdot \:30 \frac{30\left(14x-45\right)}{30}=7\cdot \:30](https://tex.z-dn.net/?f=%5Cfrac%7B30%5Cleft%2814x-45%5Cright%29%7D%7B30%7D%3D7%5Ccdot+%5C%3A30)
![14x-45=210
14x=255 14x-45=210
14x=255](https://tex.z-dn.net/?f=14x-45%3D210%0A%0A14x%3D255)
![x=\frac{255}{14} x=\frac{255}{14}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B255%7D%7B14%7D)
C. 3(x+1) /2 - x = x-4/3
![\frac{3\cdot \left(x+1\right)}{2}-x=x-\frac{4}{3} \frac{3\cdot \left(x+1\right)}{2}-x=x-\frac{4}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5Ccdot+%5Cleft%28x%2B1%5Cright%29%7D%7B2%7D-x%3Dx-%5Cfrac%7B4%7D%7B3%7D)
![\frac{3\left(x+1\right)}{2}-x-x=x-\frac{4}{3}-x \frac{3\left(x+1\right)}{2}-x-x=x-\frac{4}{3}-x](https://tex.z-dn.net/?f=%5Cfrac%7B3%5Cleft%28x%2B1%5Cright%29%7D%7B2%7D-x-x%3Dx-%5Cfrac%7B4%7D%7B3%7D-x)
![\frac{-x+3}{2}=-\frac{4}{3} \frac{-x+3}{2}=-\frac{4}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-x%2B3%7D%7B2%7D%3D-%5Cfrac%7B4%7D%7B3%7D)
![\frac{2\left(-x+3\right)}{2}=2\left(-\frac{4}{3}\right) \frac{2\left(-x+3\right)}{2}=2\left(-\frac{4}{3}\right)](https://tex.z-dn.net/?f=%5Cfrac%7B2%5Cleft%28-x%2B3%5Cright%29%7D%7B2%7D%3D2%5Cleft%28-%5Cfrac%7B4%7D%7B3%7D%5Cright%29)
![-x+3=-\frac{8}{3} -x+3=-\frac{8}{3}](https://tex.z-dn.net/?f=-x%2B3%3D-%5Cfrac%7B8%7D%7B3%7D)
![-x=-\frac{17}{3} -x=-\frac{17}{3}](https://tex.z-dn.net/?f=-x%3D-%5Cfrac%7B17%7D%7B3%7D)
![x=\frac{17}{3} x=\frac{17}{3}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B17%7D%7B3%7D)
D. x+2/2 -3 (x+1) = -5x/2 -2
![\frac{x+2}{\:2}-3\cdot \left(x+1\right)=\frac{-5x}{2}-2 \frac{x+2}{\:2}-3\cdot \left(x+1\right)=\frac{-5x}{2}-2](https://tex.z-dn.net/?f=%5Cfrac%7Bx%2B2%7D%7B%5C%3A2%7D-3%5Ccdot+%5Cleft%28x%2B1%5Cright%29%3D%5Cfrac%7B-5x%7D%7B2%7D-2)
![\frac{-5x+2}{2}-3=\frac{-5x}{2}-2 \frac{-5x+2}{2}-3=\frac{-5x}{2}-2](https://tex.z-dn.net/?f=%5Cfrac%7B-5x%2B2%7D%7B2%7D-3%3D%5Cfrac%7B-5x%7D%7B2%7D-2)
![\frac{-5x+2}{2}-3+3=\frac{-5x}{2}-2+3 \frac{-5x+2}{2}-3+3=\frac{-5x}{2}-2+3](https://tex.z-dn.net/?f=%5Cfrac%7B-5x%2B2%7D%7B2%7D-3%2B3%3D%5Cfrac%7B-5x%7D%7B2%7D-2%2B3)
![\frac{-5x+2}{2}=-\frac{5x}{2}+1 \frac{-5x+2}{2}=-\frac{5x}{2}+1](https://tex.z-dn.net/?f=%5Cfrac%7B-5x%2B2%7D%7B2%7D%3D-%5Cfrac%7B5x%7D%7B2%7D%2B1)
![\frac{-5x+2}{2}\cdot \:2=-\frac{5x}{2}\cdot \:2+1\cdot \:2 \frac{-5x+2}{2}\cdot \:2=-\frac{5x}{2}\cdot \:2+1\cdot \:2](https://tex.z-dn.net/?f=%5Cfrac%7B-5x%2B2%7D%7B2%7D%5Ccdot+%5C%3A2%3D-%5Cfrac%7B5x%7D%7B2%7D%5Ccdot+%5C%3A2%2B1%5Ccdot+%5C%3A2)
![-5x=-5x
0=0
\mathrm{Los\:lados\:son\:iguales}
\mathrm{Verdadero\:para\:todo\:x} -5x=-5x
0=0
\mathrm{Los\:lados\:son\:iguales}
\mathrm{Verdadero\:para\:todo\:x}](https://tex.z-dn.net/?f=-5x%3D-5x%0A%0A0%3D0%0A%0A%5Cmathrm%7BLos%5C%3Alados%5C%3Ason%5C%3Aiguales%7D%0A%0A%5Cmathrm%7BVerdadero%5C%3Apara%5C%3Atodo%5C%3Ax%7D)
A. x-3/2 + 7 = x - 5 - x/4
B. -3(5-x) /10 -3x/2=7 - 5x/3
C. 3(x+1) /2 - x = x-4/3
D. x+2/2 -3 (x+1) = -5x/2 -2
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años